Adventures in Chinese realism classic philosophy applied to contemporary issues - Harris, Eirik Lang; Schneider, Henrique (State University of New York Press, 2022)
"Relates Chinese Realism to contemporary political and ethical challenges, for example in international relations and the morality of the public sector"--